Effects of Manual Extrusion on Density and Texture of Churros-Inspired Kuih Keria: A Comparative Quality Analysis - Binti Hasnan, Nurul Athirah; Muhammad A’imullah Abdullah (Progress in Engineering Application and Technology, 2026)
Traditional Malaysian kuih keria, a sweet potato-based fried doughnut, faces quality inconsistencies due to variable manual shaping. Inspired by the churros extrusion method, this study investigates whether manual extrusion can standardize shape and improve product consistency while preserving authentic sensory qualities. The objectives were to measure density, analyze extrusion's influence on dough properties, and compare these with commercial samples. Using a piston-based manual extruder, dough from a traditional vendor was shaped into cylinders, fried under controlled conditions, and evaluated via oil displacement for density and a structured manual protocol for texture. Results indicated that extruded samples had a higher average density (0.803 g/cm³) than traditional samples (0.757 g/cm³) but were perceived as softer. The extrusion process yielded more uniform shapes, suggesting improved production consistency. The study concludes that manual extrusion can enhance shape regularity and offer economic benefits through reduced waste and simplified labour, presenting a viable, low-tech option for small-scale producers seeking to modernize without compromising cultural authenticity.